Blood flow analysis with computational fluid dynamics and 4D-flow MRI for vascular diseases. Issue 5 (November 2022) - Kamada, Hiroki; Nakamura, Masanori; Ota, Hideki; Higuchi, Satoshi; Takase, Kei
Abstract: Both computational fluid dynamics (CFD) and time-resolved, three-dimensional, phase-contrast, magnetic resonance imaging (4D-flow MRI) enable visualization of time-varying blood flow structures and quantification of blood flow in vascular diseases. However, they are totally different. CFD is a method to calculate blood flow by solving the governing equations of fluid mechanics, so the obtained flow field is somewhat virtual. On the other hand, 4D-flow MRI measures blood flow in vivo, thus the flow is real. Recently, with the development and enhancement of computers, medical imaging techniques, and related software, blood flow analysis has become more accessible to clinicians and its usefulness in vascular diseases has been demonstrated. In this review, we have outlined the methods and characteristics of CFD and 4D-flow MRI, respectively. We have discussed the differences in the characteristics between both methods; reviewed the milestones achieved by blood flow analysis in various vascular diseases; and discussed the usefulness, challenges, and limitations of blood flow analysis. We have discussed the difficulties and limitations of current blood flow analysis. We have also discussed our views on future directions. Graphical abstract: Unlabelled Image Highlights: CFD and 4D-flow MRI enable visualization and quantification of blood flow. CFD is a method for calculating blood flow based on medical images and assumptions. 4D-flow MRI measures blood flow in vivo. Blood flow analysis by CFD and 4D-flow MRI has demonstrated the usefulness in vascular diseases. Standardization of blood flow analysis remains a key issue to resolved for clinical use.